EFFICIENCY OF OSTEOSYNTHESIS WITH TITANIUM PLATE IN MANDIBULAR FRACTURES - Matchanov Bobur Bakhtiyor o’g’li (Web of Journals Publishing, 2024)
Trauma is an increasing global concern, with maxillofacial injuries making up a substantial portion of trauma cases. These injuries often result from road traffic accidents, interpersonal violence, falls, or contact sports. Among them, mandibular fractures are common and pose significant challenges in both functional and aesthetic restoration. The use of titanium plates for osteosynthesis has become the gold standard for managing mandibular fractures due to their superior mechanical properties and biocompatibility. This study aims to evaluate the efficacy of titanium plate osteosynthesis in the treatment of mandibular fractures.
Keywords: Mandibular fractures, Titanium plates, Comminuted fractures, Osteosynthesis, Functional recovery, Postoperative complications.